2004
DOI: 10.1128/aem.70.4.2105-2109.2004
|View full text |Cite
|
Sign up to set email alerts
|

Use of Whole Cells ofPseudomonas aeruginosafor Synthesis of the Antioxidant Hydroxytyrosol via Conversion of Tyrosol

Abstract: For the first time, a soil bacterium, designated Pseudomonas aeruginosa, was isolated based on its ability to grow on tyrosol as a sole source of carbon and energy. During growth on tyrosol, this strain was capable of promoting the formation of a significant amount of hydroxytyrosol and trace quantities of parahydroxyphenyl acetic acid and 3,4-dihydroxyphenyl acetic acid. The products were confirmed by high-performance liquid chromatography and gas chromatography-mass spectrometry analyses. Using an optimized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
73
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 32 publications
3
73
1
1
Order By: Relevance
“…5b) in the presence of L. plantarum LAB 1. Allouche et al (2004) showed that Pseudomonas aeruginosa transforms the tyrosol into hydroxytyrosol, during the phase of adaptation of growth, without consumption of these aromatic compounds. After this period, the concentration of the hydroxytyrosol decreases in the medium but the degradation of the aromatic compounds Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5b) in the presence of L. plantarum LAB 1. Allouche et al (2004) showed that Pseudomonas aeruginosa transforms the tyrosol into hydroxytyrosol, during the phase of adaptation of growth, without consumption of these aromatic compounds. After this period, the concentration of the hydroxytyrosol decreases in the medium but the degradation of the aromatic compounds Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Substituted catechols (diphenols) are important aromatic compounds and are widely used as synthons in industrial processes such as the manufacture of plastics, polymers, drugs and dyes (Allouche et al 2004;Held et al 1998;Pialis and Saville 1998;Tao et al 2004a, b). Site-specific hydroxylation of the aromatic ring for the production of these compounds can be a challenging process using conventional organic synthesis (Allouche et al 2004;Robinson et al 1992;Tao et al 2004a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Site-specific hydroxylation of the aromatic ring for the production of these compounds can be a challenging process using conventional organic synthesis (Allouche et al 2004;Robinson et al 1992;Tao et al 2004a, b). These reactions often employ expensive starting materials and exhibit poor regiospecificity resulting in low product yield (Held et al 1998;Robinson et al 1992;Tao et al 2004a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,4-Tyrosol is one of the major simple aromatic compounds present in OMW (Fernandez-Bolanos et al, 1998;Mulinacci et al, 2001) and exhibits toxicity towards several micro-organisms (Capasso et al, 1995;Sayadi et al, 2000). It has been reported that only aerobic bacteria under oxic conditions are able to oxidize 1,4-tyrosol (Allouche et al, 2004;Abdelkafi et al, 2005;Liebgott et al, 2007).…”
mentioning
confidence: 99%